Temperament Trait Changes in Japanese Black Cows Under Grazing and Confined Conditions - Nakajima, Noriaki; Mitsuishi, Hiroki; Yayota, Masato (Frontiers in Veterinary Science, 2021)
The objective of the present study was to reveal the effects of grazing on the temperament traits of cows. Nine Japanese Black cows (344 ± 32 kg body weight (BW), 7.7 ± 3.0 yr of age), which had various experiences, such as tethering, handling, and grazing, were used in this experiment. Five of the nine cows were grazed for three months on a 1.8-ha field composed of a sown pasture with forestland. The remaining cows were fed in confinement. On days 38, 52, 72, and 86 after the start of grazing, the temperament traits observed in various situations, such as moving to the body weight scale, weighing, handling, moving to the stock for blood sampling, holding in the stock, and obtaining a blood sample, were assessed with a visual analogue scale (VAS: 1-10) or score (1-5). During weighing and handling, the intensity of resistance exhibited by the grazing cows, as evaluated by head movement, walking/stepping, tail flicking, rope tension, and overall movement, was lower than that exhibited by confined cows (P < 0.05). The resistance score exhibited by the grazing cows during blood sampling was also lower than that exhibited by confined cows (P < 0.01). These results suggest that grazing enhances docility in cows with various experiences in different situations encountered in daily management.